A novel podophyllotoxin derivative with higher anti-tumor activity produced via 4′-demethylepipodophyllotoxin biotransformation by Penicillium purpurogenum. (September 2020) - Jia, Kai-Zhi; Zhan, Xia; Li, Hong-Mei; Li, Shengying; Shen, Yuemao; Qingsheng, Qi; Zhang, Youming; Li, Yue-zhong; Tang, Ya-Jie
Graphical abstract: Highlights: 4′-d-β-DMEP was isomerized into the novel product 4′-d-α-DMEP with 43.09% conversion. The IC50 value of 4′-d-α-DMEP on tumor cells MCF-7 was significantly reduced by 11.27 and 17.34 times than 4´-d-β-DMEP and VP-16. The model for transforming 4'-d-β-DMEP into 4'-d-α-DMEP by P. purpurogenum ACCC 32170 was provided. Abstract: Biological modification of natural products is an important approach to improve the pharmacological properties. 4′-d-β-Demethylepipodophyllotoxin (4′-d-β-DMEP), a typical natural lignin, is used as the aglycon of topoisomerase inhibitor etoposide (VP-16). In this study, 4′-d-β-DMEP was isomerized into the novel product 4′-d-α-DMEP with 43.09% conversion by P. purpurogenum ACCC 32170. 4′-d-α-DMEP was largely produced extracellularly in the late fermentation stage, which was accompanied with the decrease of dry cell weight and the increase of culture pH. A constitutively expressed cytosolic enzyme was involved in the transformation and functioned when culture pH ranged from 7.0–10.0. The IC50 value of 4′-d-α-DMEP was around 0.80 μM against tumor cells MCF-7, which was significantly reduced by 11.27 and 17.34 times than 4′-d-β-DMEP (i.e., 9.82 μM) and VP-16 (i.e., 14.67 μM). This study provided the novel podophyllotoxin derivative with higher anti-tumor activity and microbial transformation process, which would promote transferring lignans into the clinic trial.